Statutory Challenges Affecting the Enforcement of the Insider Trading Prohibition in Zimbabwe: Array - Chitimira, Howard (Acta Universitatis Danubius. Juridica, 2021)
Various challenges have to date marred the effective and consistent enforcement of the insider trading prohibition in Zimbabwe. As a result, the regulation of insider trading has remained flawed and problematic in Zimbabwe since the early 1980s to date. For instance, the Zimbabwean anti-insider trading regulatory framework has so far failed to curb insider trading activities owing to several statutory flaws that are imbedded in the Securities Act 17 of 2004 [Chapter 24:25] as amended (Securities Act), such as poor insider trading penalties, inadequate and flawed insider trading provisions and insufficient definitions of key terms for insider trading offences and related aspects. These and other flaws have negatively affected market efficiency, market integrity and public investor confidence in the Zimbabwean financial markets. Consequently, the article exposes the statutory flaws and challenges that are affecting the regulation and combating of insider trading in the Zimbabwean financial markets. Thereafter, possible measures that could be adopted by the relevant authorities to enhance the regulation and enforcement of the Zimbabwean anti-insider trading prohibition are provided.